Community of trauma care partnering with stakeholders to improve injury outcomes: survey analysis and panel development - Deborah M Stein; Elliott R Haut; Michelle A Price; Pam J Bixby; Rochelle A Dicker; Rosemary A Kozar; Princess Fortin; Ashley N Moreno; Rachel D Appelbaum; Katherine Joseph; Morgan Hennessy; Sue Prentiss; et al. (Trauma Surgery & Acute Care Open)
Background In June 2021, the Injury Research Engagement Project (I-REP) was established. In 2022, we preformed focus group analysis with patients/caregiver and researchers that resulted in themes in preferences, motivations, and best practices to increase participation in trauma research. The importance of trust and well-established relationships was common across all groups. In this study, we aimed to further evaluate preferences regarding research procedures and outcomes, and develop a panel for sustained patient engagement.Methods We performed a multiphase, mixed methods study to elicit trauma stakeholders’ perspectives regarding aspects of research. Previously published phase 1 involved focus group analysis. Phase 2 vignette-based surveys and phase 3 panel formation are described here. One survey was completed by patients/caregivers, and the second by trauma researchers. We compared the responses using independent t-tests. This was followed by a webinar and development of an I-REP panel of patients/caregivers.Results 60 patients/caregivers and 114 researchers participated in the online surveys, with completion rates of 68% and 69%, respectively. The majority of patients/caregivers were >45 years, female (66.7%), and >3 years out from their or their family member’s injury (68.6%). The majority of the researchers were >35 years and male (56.2%). Participants were asked to gauge their perceptions of different research scenarios. The analysis identified themes emerging across groups. Several survey findings differed from phase 1, including motivations to participate (payment) and consent preferences (timing, approach). Racial and ethnic demographics of the participants were not collected.Conclusions Engaging trauma stakeholders results in research more relevant to patients’ needs and priorities. Qualitative engagement methods that intentionally include a more diverse population and determining the appropriate format for specific questions may lead to results that are be more generalizable. The educational webinar was well received, and several participants opted to serve as I-REP panelists to collaborate with trauma researchers moving forward.Level of evidence IV.